2010
DOI: 10.1007/s10209-010-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

e-Government online forms: design guidelines for older adults in Europe

Abstract: This paper reports on the findings of Delivering Inclusive Access to Disabled and Elderly Members of the community (DIADEM), a 3-year project, funded by the European Commission's Sixth Framework Programme, to assist older adults when accessing, completing, and submitting online forms, by developing web-based assistive technologies that adapt the online form according to users' needs. A user-centred approach is adopted to gain insights into the challenges faced by 80 older adults in three European countries as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This is particularly valuable given that, to date, insufficient explanation and notification of home adaptations during home visits has resulted in some users feeling dissatisfied with their experience resulting in equipment abandonment levels in excess of 50 % [ 12 ]. Enabling people to stay at home and maintain independence at home can add to an increased sense of control and improved quality of life [ 59 61 ]. Interestingly evidence from a study involving older adults from eleven European countries found that older adults wanted to have a trusting relationship with the practitioners, to be respected about their preferences, and to receive clear health information from the healthcare providers [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly valuable given that, to date, insufficient explanation and notification of home adaptations during home visits has resulted in some users feeling dissatisfied with their experience resulting in equipment abandonment levels in excess of 50 % [ 12 ]. Enabling people to stay at home and maintain independence at home can add to an increased sense of control and improved quality of life [ 59 61 ]. Interestingly evidence from a study involving older adults from eleven European countries found that older adults wanted to have a trusting relationship with the practitioners, to be respected about their preferences, and to receive clear health information from the healthcare providers [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly valuable given that, to date, insufficient explanation and notification of home adaptations during home visits has resulted in some users feeling dissatisfied with their experience, resulting in equipment abandonment levels in excess of 50% [ 12 , 51 , 52 ]. Enabling people to stay at home and maintain independence at home can add to an increased sense of control and improved quality of life [ 53 - 55 ]. The OTs that took part in this study did not seem to be concerned about the usability of the software but rather were more interested in the impact of using a VRIDA as a tool to assist in occupational therapy interventions and the positive impact this would have on the patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, many guidelines for the design of web forms can be applied [3,5,15,33]. The guidelines include design requirements considering the needs of increasingly aging users [21,23] or approaches to improve the accessibility of government forms for handicapped people [19]. Despite this research on designs of forms, their complexity is still an open issue.…”
Section: Forms In Actionmentioning
confidence: 99%